Measurement procedure of the diffusion coefficients in gases by the two-flask method - Zhavrin, Y.I.; Kossov, V.N.; Fedorenko, O.V.; Asembaeva, M.K.; Mukamedenkyzy, V. (Recent Contributions to Physics, 2013)
Two-flask method to measure diffusion coefficients in gases in isothermal conditions at the atmospheric pressure is examined. The given method is a classical quasi-stationary method, which is used in the measurement of mutual diffusion coefficients, self-diffusion, thermal diffusion, the study of the diffusion baroeffect in a wide range of parameters (pressure, temperature, concentration), as well as in the study of multicomponent diffusion and instability of the mechanical equilibrium in multicomponent gas mixtures. Described the scheme and construction of two-flask apparatus, also the machine with the viewing windows in the flasks and in the central part of the diffusion path, which allowed visualize the convective flows arising from an unstable diffusion using the shadow tool. Represented the sequence of experimental procedure. Examined quantitative determination of gas mixtures composition after diffusion. Calculation of the diffusion coefficients is shown and the errors analysis of measurement of the concentrations by interferometer and chromatograph is given. Discussed errors in determining the geometric characteristics and volume of the diffusion path of the upper and lower flasks and associated with them so-called “instrument constant”. Shows the definition of an instrument constant using either “absolute” or “relative” methods. The resultant error analysis of the diffusion coefficients is presented. Were shown results of the observations belonging to the normal law of distribution in the measurement of diffusion coefficients of hydrogen-nitrogen system.